2021
DOI: 10.7759/cureus.18503
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Cycle Deliberate Practice in Virtual Reality: Teaching Transvenous Pacemaker Insertion to Emergency Medicine Residents

Abstract: IntroductionTransvenous pacemaker insertion is a critical life-saving procedure that is infrequently performed. Traditional mannequin-based training paradigms are resource intensive and sometimes inadequate due to time constraints. Rapid Cycle Deliberate Practice (RCDP) is an effective teaching modality for highly scripted procedures. We propose using a simulation-based technique of RCDP in virtual reality (VR) to teach this procedure. MethodsSixteen emergency medicine residents were recruited. A pre-survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…We found that simulation participation significantly increased resident knowledge and confidence when dealing with pediatric cardiac arrest. Our results are like those reported elsewhere, finding that participation in mock code is an effective educational method to increase pediatric resident knowledge and self-confidence in managing pediatric arrest 8–10 . We did not show any additional benefit in adding traditional education or reinforced education.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We found that simulation participation significantly increased resident knowledge and confidence when dealing with pediatric cardiac arrest. Our results are like those reported elsewhere, finding that participation in mock code is an effective educational method to increase pediatric resident knowledge and self-confidence in managing pediatric arrest 8–10 . We did not show any additional benefit in adding traditional education or reinforced education.…”
Section: Discussionsupporting
confidence: 88%
“…Our results are like those reported elsewhere, finding that participation in mock code is an effective educational method to increase pediatric resident knowledge and self-confidence in managing pediatric arrest. [8][9][10] We did not show any additional benefit in adding traditional education or reinforced education.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Obstetric Life Support instructors lead participants through different training scenarios using Rapid Cycle Deliberate Practice, 18 an instructional methodology to teach resuscitation and team skills. Each participant practices hands-on techniques with a customized, low-fidelity simulator with real-time feedback on critical maternal cardiac arrest skills.…”
Section: Methodsmentioning
confidence: 99%
“…(See appendix for sample case information) Innovative teaching with Rapid-cycle deliberate practice simulation: The faculty used an innovative teaching approach, which has previously shown very effective teaching in small group settings. Rapidcycle deliberate practice simulation sessions (RCDP) are a simulation method that involves frequent pauses to give targeted feedback to learners and allows opportunities for repetitive practice improvement (13). Module 2b (a 3h): Paediatric trauma simulation, covering the evaluation and management of injuries such as fractures, head injuries, and abdominal injuries.…”
Section: Curriculum Developmentmentioning
confidence: 99%